New estimation of private returns to higher professional education and training - Cattaneo, M. Alejandra [Verfasser] (My University, 2011)
"In this paper, a cost-benefit type of analysis is used to determine the rate of returns to education for the specific case of professional education and training (PET), differentiating for the two types of PET education offered in Switzerland. In contrast to the Mincer-type of analysis, the cost-benefits calculations allow to include the costs of education, direct and indirect, and the risk of unemployment. The net benefits of the PET program are estimated by calculating the discounted wages over the lifecycle, minus lost wages in case of unemployment, and the costs of education for individuals. These net benefits are then compared to those of individuals with upper secondary vocational education. The Swiss Labor Force Survey (SLFS) 1996-2009 is used in this analysis. The panel structure of the SLFS allows to calculate lower bounds of the wage gains, correcting thereby the endogeneity of the educational choice. The results show that, independent of the amount of financial support, individuals completing a PET have significant net-wage gains." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 3.1.3 Studienqualifizierende Bildungsgänge; I 2.2.1 Westeuropa; Höhere Berufsbildung; Kosten-Nutzen-Analyse; Bildungsertrag; Einkommenseffekte; Arbeitsmarktrisiko; Schweiz